The influence of substitution strategies on the physical match performance of elite female field hockey players - Sparks, M. (International Journal of Performance Analysis in Sport, 2024)
The study aims were to i) compare movement demands of different substitution strategies for each position in elite female field hockey and ii) compare the effect substitutions had on match intensities post-substitution. During 19 international matches, movement data from 26 international players were collected. Substitution strategies were categorised into 5-min, 7.5-min, 10-min, at random intervals and full quarter play. Small reductions in work-rate were found from quarter 1 to 4 across positions despite running intensities not differing between quarters. Work-rate was greater for starting players during the opening minute and was also higher when compared to players coming off the bench. However, players coming off the bench had higher running intensities during this first minute with higher work-rates after minute two compared to the quarter average. Small differences in work-rate were found between substitution strategies for strikers and midfielders, with no differences in intensity for any position. In conclusion, a decrease in work-rate during the match suggests fatigue, but because intensity was maintained throughout, pacing strategies could be present. Although the substitution strategy utilised did not produce substantial results, the "first-minute-rush-effect" was confirmed as players coming off the bench were able to match and, in some cases, increase the work-rate.